Decision feedback differential detection for differential orthogonal space-time modulation with APSK signals over flat-fading channels. - Aijun Song
Differential orthogonal space-time modulation (DOSTM) with amplitude/phase shift keying (APSK) signals has been recently proposed to improve the data throughput of the DOSTM with PSK signals over quasi-static channels. In this letter, decision feedback differential detection (DF-DD) based on linear prediction is presented for the DOSTM with APSK Signals (DOSTM-APSK) over flat-fading channels. The proposed DF-DD offers better performance than the differential detection when the channel experiences fast fading. The coefficients of the linear prediction based DF-DD can be obtained by an adaptive recursive least-squares algorithm, where the channel statistics are not needed. The proposed DF-DD is also applicable to the general unitary differential space-time modulation.
Keywords: APSK signal; Adaptive recursive least-squares algorithm; Amplitude-phase shift keying; Channel statistics; Decision feedback differential detection; Differential orthogonal space-time modulation; Flat-fading channel; General unitary differential space-time modulation; Linear prediction; Quasi-static channel